2020
DOI: 10.3389/fpsyg.2020.572099
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Learning Difficulties in Reading and Mathematics: The Role of Intelligence and In-Class Attentive Behavior

Abstract: The goal was to identify the domain-general cognitive abilities and academic attitudes that are common and unique to reading and mathematics learning difficulties that in turn will have implications for intervention development. Across seventh and eighth grade, 315 (155 boys) adolescents ( M age = 12.75 years) were administered intelligence, verbal short-term and working memory, and visuospatial memory, attention, and ability measures, along with measures of English and mathematics attit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 101 publications
(161 reference statements)
0
3
0
1
Order By: Relevance
“…Finally, we expected that the contribution of WM would extend across the three grades (Peng et al, 2018) and could be related to verbal tasks to a greater extent (Cirino et al, 2015;Cai et al, 2013). Furthermore, we predicted that higher fluid intelligence could act as a protective factor against MD across the three grades (Geary et al (2020). Furthermore, slower processing speed could constitute a risk factor for presenting MD in situations in which the selection tasks involve arithmetic, as in grade 2 (e.g., Cirino et al, 2015;Vukovic & Siegel, 2010).…”
Section: The Current Studymentioning
confidence: 91%
See 1 more Smart Citation
“…Finally, we expected that the contribution of WM would extend across the three grades (Peng et al, 2018) and could be related to verbal tasks to a greater extent (Cirino et al, 2015;Cai et al, 2013). Furthermore, we predicted that higher fluid intelligence could act as a protective factor against MD across the three grades (Geary et al (2020). Furthermore, slower processing speed could constitute a risk factor for presenting MD in situations in which the selection tasks involve arithmetic, as in grade 2 (e.g., Cirino et al, 2015;Vukovic & Siegel, 2010).…”
Section: The Current Studymentioning
confidence: 91%
“…The role of intelligence in MD is not clearly defined because most studies rule out students with low IQ in their initial screenings (see Agostini et al, 2022, for a review). Nevertheless, some studies have reported differences between TA and MD students on verbal and nonverbal intelligence tasks (e.g., Andersson, 2010;Geary et al, 2020; but see Andersson, 2008) and that it was a key factor in classifying students in terms of mathematics achievement (Geary et al, 2020). In addition, during the early primary grades, the importance of processing speed in the acquisition of arithmetic skills has been highlighted (e.g., Bull & Johnston, 1997;Fuchs et al, 2006), and the low processing speed of students with MD has been repeatedly reported (e.g., Cirino et al, 2015;Vukovic & Siegel, 2010; but see Chan & Ho, 2010).…”
Section: Efs Intelligence Processing Speed and Mathematical Difficultiesmentioning
confidence: 99%
“…Kesulitan atau faktor belajar yang dialami siswa dapat disebabkan oleh faktor internal dan faktor eksternal (Geary, 2020;Hamukwaya, 2021;Hebert, 2019;Rodríguez, 2019). Faktor internal adalah faktor yang berasal dari dalam diri siswa, misalnya kesehatan, bakat minat, motivasi, intelegensi dan sebagainya.…”
Section: Pendahuluanunclassified
“…Little research has directly compared the cognitive abilities in dyscalculia and dyslexia. The studies targeted the investigation of symbolic and non-symbolic numerical magnitude, phonological awareness, attention, verbal short-term memory, visuospatial memory, lexical access, and working memory ( Geary et al, 2020 ; Grant et al, 2020 ). Peters et al (2020) demonstrated that children with dyscalculia had a marked deterioration in spatial skills in comparison to their typically developing peers.…”
Section: Introductionmentioning
confidence: 99%